(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research explores the role of financial literacy and digital technology in financial decision making in the digital era. Strong financial literacy has been proven to have a positive impact on individual financial well-being, especially in facing the economic challenges caused by the COVID-19 pandemic. However, there are still challenges in achieving optimal financial literacy in the digital era, such as the digital divide and lack of adequate financial literacy. Therefore, efforts to improve financial literacy, especially through educational initiatives, are critical. The implication of this research is that the integration of financial and digital literacy in the education curriculum as well as building community capacity can help individuals to be better prepared to face the challenges and opportunities in the digital era.